Reconceptualizing the Elements of Well-Known Trademarks in Trademark Registration in Indonesia, Italy, and the United States: Merekonseptualisasi Kembali Unsur-Unsur Merek Terkenal dalam Pendaftaran Merek di Indonesia, Italia, dan Amerika Serikat - Kesya Fadhilah Azzahra; Rianda Dirkareshza (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Well-known trademarks require legal protection to preserve exclusive rights, reputation, and fair market competition. Specific Background: This study compares protection models in Indonesia, Italy, and the United States. Knowledge Gap: Indonesian trademark regulation still lacks explicit and comprehensive provisions on dilution, judicial precedent, blurring, tarnishment, unfair advantage, and likelihood of confusion. Aims: This study analyzes the protection of well-known trademarks through comparative legal analysis using normative juridical and case approaches. Results: Italy and the United States provide broader safeguards through dilution-related doctrines that protect reputation, distinctiveness, and commercial identity, while Indonesia has progressed under Law No. 20 of 2016 but still requires clearer standards and stronger examination guidelines. Novelty: The study proposes reconceptualizing Indonesian well-known trademark protection by adopting explicit dilution provisions and structured assessment criteria. Implications: Future amendments should strengthen legal certainty, prevent bad faith registration, support fair competition, and maintain consumer trust. Highlights: Italy and the United States provide broader safeguards. Judicial precedent needs clearer regulatory recognition. Bad faith registration remains a key concern. Keywords: Well-Known Trademark, Famous Mark, Trademark Law